ANXA11 mutations are associated with amyotrophic lateral sclerosis–frontotemporal dementia - Wang, Yu; Duan, Xiaohui; Zhou, Xiao; Wang, Renbin; Zhang, Xiangfei; Cao, Zhenhua; Wang, Xiaoxia; Zhou, Zhi; Sun, Yu; Peng, Dantao (Frontiers in Neurology, 2022)
Background: The Annexin A11 (ANXA11) gene has been newly identified as a causative gene of amyotrophic lateral sclerosis (ALS) with or without frontotemporal dementia (FTD). The current study aimed to investigate the ANXA11 mutations in a Chinese ALS-FTD or FTD cohort. Methods: Ten probands/patients with suspected ALS-FTD or FTD were included. Mutational analysis of ANXA11 was performed through Next Generation Sequencing (NGS) and Sanger sequencing. We reviewed the clinical presentation, neuropsychology test results, brain imaging findings, and electrophysiological examination findings. Results: Six probands presented with ALS-FTD, and four with behavior variant FTD (bv-FTD). We identified a non-synonymous heterozygous mutation (c.119A>G, p.D40G) of ANXA11 in proband 1, which is associated with ALS,. However, this is the first report of the mutation causing ALS-FTD. Proband 1 initially presented abnormal behaviors and later progressed to classic upper motor nervous system damage in the bulbar and limbs. Magnetic resonance imaging (MRI) showed significant bilateral temporal lobe atrophy and bilateral signal hyperintensities along the corticospinal tracts. 18F-AV45-PET imaging showed negative amyloid deposits. Conclusion: ANXA11-related diseases have high clinical and genetic heterogeneity. Our study confirmed the contribution of ANXA11 mutations to ALS-FTD. The ANXA11 mutations established a complex genotype-phenotype correlation in ALS-FTD. Our research further elucidated the genetic mechanism of ALS-FTD and contributed to setting the foundation of future targeted therapy.